Five-year dynamics of carotid artery remodeling in hypertensive patients working on a fly-in/fly-out basis in the Arctic - N. P. Shurkevich; A. S. Vetoshkin; L. I. Gapon; A. A. Simonyan (Кардиоваскулярная терапия и профилактика)
Aim. To analyze the 5-year dynamics of atherosclerotic remodeling of common carotid arteries (CCA) in persons with hypertension (HTN) working on a fly-in/fly-out basis in the Arctic. To determine sex characteristics, factors associated with atherosclerotic plaque (ASP) imaging, and outcome endpoints.Material and methods. In the period 2012-2017, 372 (men, 273; women, 99) employees with grade 1-2 HTN working on a fly-in/fly-out basis in the Arctic were observed. Depending on the ultrasound data, the subjects were divided into 2 groups: with an initially normal CCA wall (men, 137; women, 65) and with subclinical carotid atherosclerosis (SCA) in the form of intima-media thickness (IMT) increase >0,9 mm (men, 136; women, 34) without differentiable ASPs. The dynamics of CCA wall remodeling was analyzed depending on sex, the level of mean 24-hour blood pressure (BP) and echocardiography data on the left ventricular (LV). Factors associated with the identification of ASPs and endpoints were determined.Results. Men with HTN were significantly more likely to have SCA than women. The frequency of ASP imaging directly depended on the initial CCA characteristics and was higher in both sexes with IMT increase. The level of mean 24-hour BP insignificantly influenced the atherosclerosis severity. According to the 5-year follow-up, the structure of CCA wall changed significantly more often in men than in women. In individuals with concentric LV hypertrophy, regardless of the initial CCA state, the highest prevalence of ASP was recorded. The progression of the atherosclerotic process was more intense in individuals with concentric remodeling and normal LV geometry in combination with IMT increase. In individuals with initial atherosclerosis of CCA, acute myocardial infarction and acute cerebrovascular accident developed significantly more often than in patients with initially normal CCA walls.Conclusion. Under the fly-in/fly-out conditions in the Arctic, in hypertensive men significantly more often than in women, SCA was detected and was characterized by more intense progression during 5-year follow-up. In men, it was significantly more often accompanied by cardiovascular complications. It is important to identify signs of SCA for early initiation of therapy in order to prevent fatal cardiovascular events in Arctic workers.